A pH Scale for the Protic Ionic Liquid Ethylammonium Nitrate. Issue 21 (13th April 2016) - Kanzaki, Ryo; Kodamatani, Hitoshi; Tomiyasu, Takashi; Watanabe, Hikari; Umebayashi, Yasuhiro
Abstract: To quantify the properties of protic ionic liquids (PILs) as acid–base reaction media, potentiometric titrations were carried out in a neat PIL, ethylammonium nitrate (EAN). A linear relationship was found between the 14 p K a  values of 12 compounds in EAN and in water. In other words, the p K a  value in EAN was found to be roughly one unit greater than that in water regardless of the charge and hydrophobicity of the compounds. It is possible that this could be explained by the stronger acidity of HNO3 in EAN than that of H3 O + in water and not by the difference in the solvation state of the ions. The pH value in EAN ranges from −1 to 9 on the pH scale based on the pH value in water. Abstract : Tipping the pH scale : By using potentiometric acid–base titrations, a pH scale applicable to the protic ionic liquid ethylammonium nitrate (EAN) was determined. This water‐based pH scale can be employed to directly compare the differences in H + activity between EAN and water. For example, the H + activity in the neutral EAN corresponds to the aqueous solution with pH=4.